2004
DOI: 10.1016/j.seares.2004.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal zonation patterns and feeding structure of marine nematode assemblages on a macrotidal, ultra-dissipative sandy beach (De Panne, Belgium)

Abstract: Horizontal zonation pa tterns and feeding structure of marine nematode assemblages on a macrotidal, ultra-dissipative sandy beach (De Panne, Belgium) Journal of Sea Research 52:211-226 ABSTRACTMacrobenthic zonation on sandy beaches has been studied widely, whereas meiobenthic/nematofaunal species richness and zonation pa tterns have received little a ttention. We investigated community structure, inte rt idal zonation of nematode species and feeding structure across a macrotidal, ultra-dissipative, sandy be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
47
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 38 publications
11
47
1
Order By: Relevance
“…Analysed results of the trophic structure of free-living nematode communities in this study were also found in the same line with the study of Gheskiere, et al (2004) [23], in a tourists impacted sandy beach of the De Panne, Belgium. The authors reported that non-selective deposit feeders dominated all of the zones, except in the drift line, where epistratum feeders were dominant on sandy beaches.…”
Section: Discussionsupporting
confidence: 88%
“…Analysed results of the trophic structure of free-living nematode communities in this study were also found in the same line with the study of Gheskiere, et al (2004) [23], in a tourists impacted sandy beach of the De Panne, Belgium. The authors reported that non-selective deposit feeders dominated all of the zones, except in the drift line, where epistratum feeders were dominant on sandy beaches.…”
Section: Discussionsupporting
confidence: 88%
“…6A). Most nematodes are nonselective deposit-feeders (Gheskiere et al 2004) using labile organic matter (Moens et al 2002). Our results suggest that phytodetritus or MPB was not readily assimilated and that nematodes might depend on microbenthic organisms that rely on MPB or phytodetritus.…”
mentioning
confidence: 78%
“…The dominance of Xyalidae and the low number of nematode species also reflect the sediment grain size of Fazenda beach. A high abundance of Xyalidae in sandy beaches composed of fine-grained sediments was already evidenced by Gheskiere et al (2004), Hourston et al (2005) and Gourbault and Warwick (1994). In addition, fine sediment has a low diversity of nematodes and is generally inhabited by non-selective deposit feeders , which includes members of Xyalidae.…”
Section: Colonisation Patternmentioning
confidence: 98%